Comparison of horizontal and vertical electric field in the treatment of river sediment by electro-dewatering. Issue 6 (26th April 2019) - Wu, Pan; Zhan, Fuxin; Wang, Zheng; Li, Qunqun; Li, Jianfeng; Xiong, Ziming; Shi, Yafei; Pi, Kewu; Liu, Defu; Gerson, Andrea R.
Abstract: The aim of this study was to evaluate and compare the effectiveness of horizontal ( H-EDW ) and vertical ( V-EDW ) electro-dewatering fields, in terms of dewatering and energy consumption, for the treatment of river sediment. The influence of the sludge thickness (3, 4, 5, 6, 7 cm) and the applied voltage (10−30 V) were examined. V-EDW was found to significantly improve dewatering and reduce process time, while H-EDW has the potential to save energy but results in sludge containing greater moisture. As the applied voltage was increased from 10 V to 30 V, the final dry solids content and energy consumption increased for both modes. Increased sludge thickness from 3 cm to 7 cm was found to have a negative influence on the final dry solid content of the sludge for V-EDW, but is not a significant influence with H-EDW . The results demonstrate that H-EDW is an effective dewatering method and has potential for continuous operation and energy efficiency for industrial-scale applications.